Biosynthesis of Fusarubins Accounts for Pigmentation of Fusarium fujikuroi Perithecia - Studt, Lena (American Society for Microbiology, 2012)
Fusarium fujikuroi produces a variety of secondary metabolites, of which polyketides form the most diverse group. Among these are the highly pigmented naphthoquinones, which have been shown to possess different functional properties for the fungus. A group of naphthoquinones, polyketides related to fusarubin, were identified in Fusarium spp. more than 60 years ago, but neither the genes responsible for their formation nor their biological function has been discovered to date. In addition, although it is known that the sexual fruiting bodies in which the progeny of the fungus develops are darkly colored by a polyketide synthase (PKS)-derived pigment, the structure of this pigment has never been elucidated. Here we present data that link the fusarubin-type polyketides to a defined gene cluster, which we designate fsr, and demonstrate that the fusarubins are the pigments responsible for the coloration of the perithecia. We studied their regulation and the function of the single genes within the cluster by a combination of gene replacements and overexpression of the PKS-encoding gene, and we present a model for the biosynthetic pathway of the fusarubins based on these data.